PTH-013 Comparison of the first and second round of colorectal cancer screening in northeast England. (23rd September 2015) - Rees, C J; Rutter, M; Dempsey, N J; Waddup, G; Ritchie, M C; Singh, J N; Nylander, D L; Painter, J E; Ward, I; Clifford, G M
Abstract : Introduction: South of Tyne and Tees bowel cancer screening centres commenced screening in February 2007 as first wave centres. They serve a combined population of 1.5 million. The aims of the prospective audit were 1. To analyse the findings at colonoscopy among individuals with positive FOB in round 2 of screening and correlate this with their own results from round 1 of screening and 2. To compare findings at the first and second round of screening. Methods: A prospective audit of all patients with a positive FOB screened in round one and two and undergoing colonoscopy was undertaken. For individuals undergoing the second round of screening a comparison was made with their first round of screening 2 years earlier. Individuals with an abnormal FOB result (5/6 positive windows) or a weak positive result (initial test indeterminate and subsequent strong positive or indeterminate) are invited for colonoscopy. Individuals with an initial indeterminate result then two normal FOB's are invited for repeat FOB testing in 2 years time. Results: 1490 patents were colonoscoped between 2007 and 2009 in the first round of screening and subsequently 118 patients since the second round commenced in April 2009. Of the 118 scoped as part of their second round, 109 had a negative FOB in round 1, of which six were diagnosed with cancer and nine with high-risk polyps in round 2. A further 29 had low or intermediate risk polyps, 21 abnormal not polyps and 34 were normal. Of the six patients who had weak positive then 2 normals in round 1, 3 had low or intermediate risk polyps, 1 abnormal not polyps and 2 normal. Of 3 patients with positive FOBs (colonoscoped) in round 1, 1 had low risk polyps and 2 were abnormal but not polyps in round 2. Abstract 013 compares overall findings of screening in round 1 and 2 demonstrating that cancer diagnosis was more likely in round 1. Conclusion: Round 2 of screening demonstrated a high yield of pathology including six patients with cancer and nine with high-risk polyps. All of these patients had completely negative FOBs in round 1. A diagnosis of cancer was more likely in round one. Abstract submitted on behalf of the Northern Region Endoscopy Group.